2018
DOI: 10.1371/journal.pone.0191721
|View full text |Cite
|
Sign up to set email alerts
|

Severe community-acquired pneumonia: Characteristics and prognostic factors in ventilated and non-ventilated patients

Abstract: BackgroundPatients with severe community-acquired pneumonia (SCAP) and life-threatening acute respiratory failure may require invasive mechanical ventilation (IMV). Since use of IMV is often associated with significant morbidity and mortality, we assessed whether patients invasively ventilated would represent a target population for interventions aimed at reducing mortality of SCAP.MethodsWe prospectively recruited consecutive patients with SCAP for 12 years. We assessed the characteristics and outcomes of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
84
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 34 publications
6
84
0
10
Order By: Relevance
“…Indeed, even the propensity-adjusted multivariate analysis did not show an association between ARDS and patient mortality. According to our results, we think that the expected association of ARDS with mortality seems more related to the need for mechanical ventilation in these patients with CAP rather than ARDS itself, as we have recently reported that invasive mechanical ventilation in patients with severe CAP independently predicts mortality [36]. However, we cannot exclude that specific populations of patients with CAP and ARDS may have different mortality, since subphenotypes of ARDS patients with different outcomes related to inflammation [37] or fluid responsiveness [38] have been proposed.…”
Section: Discussionsupporting
confidence: 56%
“…Indeed, even the propensity-adjusted multivariate analysis did not show an association between ARDS and patient mortality. According to our results, we think that the expected association of ARDS with mortality seems more related to the need for mechanical ventilation in these patients with CAP rather than ARDS itself, as we have recently reported that invasive mechanical ventilation in patients with severe CAP independently predicts mortality [36]. However, we cannot exclude that specific populations of patients with CAP and ARDS may have different mortality, since subphenotypes of ARDS patients with different outcomes related to inflammation [37] or fluid responsiveness [38] have been proposed.…”
Section: Discussionsupporting
confidence: 56%
“…After the initial diagnosis of CAP, the biggest challenge in the emergency department is to promptly recognize patients who might develop respiratory failure and multiple organ dysfunctions. Patients requiring mechanical ventilation or vasopressor support should be admitted to ICU as soon as possible, as delays in ICU admission have been related to worse outcomes [16][17][18].…”
Section: Why Is Community-acquired Pneumonia Severity Assessment Impomentioning
confidence: 99%
“…Severe CAP (SCAP) has generally been defined as CAP requiring admission to the intensive care unit due to invasive mechanical ventilation or septic shock requiring vasopressors [4][5][6]. It is related to severe mortality and approximately 16-36% patients with SCAP may die in a short time [7]. It is reported that about one-third of patients with CAP requiring hospitalization present with co-infection of both bacteria and virus, and most of them are Streptococcus pneumoniae (S. pneumoniae) and influenza [8].…”
Section: Introductionmentioning
confidence: 99%